(untitled) - World Health Organization (Rome, 2008)
Food labelling is the primary means of communication between the producer and seller of food on one hand and the purchaser and consumer on the other,..
Keywords: Natural foods,Thực phẩm tự nhiên,Organic foods,Thực phẩm hữu cơ; Standards,Tiêu chuẩn